Avaliação de riscos ambientais no Aeroporto Internacional de Viracopos, Campinas (SP) - Carra, Thales Andrés [UNESP]; Da Conceição, Fabiano Tomazini [UNESP]; Teixeira, Bruno Bernardes (My University, 2012)
Considering the current context of environmental concern, the main purpose of this research was to develop and apply indicators to evaluate the environmental risk for airports. As a result, 19 indicators related to storage and handling dangerous substances were created. These indicators represent five conditions varying from the worst (level 1) to the ideal condition (level 5). The indicators were applied, as a study of case, at Viracopos International Airport, Campinas (SP). The results showed a medium performance of 2.3, using a scale raging from 1.0 to 5.0, characterized as 'critical'. Then, the indicators were analyzed to determine the major weaknesses related to the environmental management at Viracopos International Airport, as well as to identify good practices and solutions. Among the suggested management strategies, we highlight the suitability of areas for storage of dangerous substances. In general, it can be inferred that the indicators proposed in this paper to evaluate the performance in the management of environmental risks at the Viracopos International Airport and propose actions to prevent, monitor, correct, and mitigate the environmental impacts of its operations.
Evaluation of environmental risk at Viracopos International Airport, Campinas (SP)
Keywords: Airport; Environmental management; Environmental risk